Стан систем безпеки з використанням технічних засобів відеозапису та відеоспостереження: зарубіжний досвід, перспективи впровадження в діяльність Національної поліції України - Коршенко, В. А.; Korshenko, V. A.; Чумак, В. В.; Chumak, V. V.; Мордвинцев, М. В.; Mordvyntsev, M. V.; Пашнєв, Д. В.; Pashnev, D. V.; Мордвинцев Микола Володимирович; Дмитро Пашнєв (Право і безпека. - 2020. - № 2 (77). - С. 86-92, 2020)
Розглянуто стан систем відеозапису та відеоспостереження, які використовуються для забезпечення публічної безпеки у великих містах України. Проаналізовано системи і напрямки розвитку систем безпеки з використанням відеозапису та відеоспостереження в розвинених країнах світу. Запропоновано шляхи модернізації та подальшого розвитку систем безпеки в Україні.

Tendencies in the development of intelligent video surveillance systems in developed countries have been analyzed. It has been found out that such countries (EU, USA, China, Russia) install modern “smart” CCTV cameras, the information from which is sent to modern situational centers, where it is processed by using artificial intelligence, neural networks and cloud infrastructure. Certain types of cameras even have the ability to independently process the received information. This makes it possible to perform biometric facial recognition, to detect behavioral abnormalities of suspects who intend to commit offenses; to record the appearance and disappearance of objects, to recognize the state car plates, to recognize their type, brand and color, to record the way of their movement, to carry out the analysis of these factors on the basis of these factors to search for suspects and cars in the city. Video surveillance centers, in particular within one of the most important areas of public safety – traffic safety – have the ability to recognize prohibited or atypical traffic, to capture the intersection of the restricted area or the intersection of the visual line, to respond to the passage of people in a given direction, to identify traffic conditions, to detect traffic density, congestion and mass congestion of vehicles, to respond to the appearance of people in the surveillance zone, etc. Based on the review of the experience of introduction and use of video surveillance systems in Ukraine and analysis of their development in developed countries, the authors have suggested the ways to modernize and further develop security systems in Ukraine by using CCTV cameras.

Рассмотрено состояние систем видеозаписи и видеонаблюдения, используемых для обеспечения общественной безопасности в крупных городах Украины. Проанализированы системы и направления развития систем безопасности с использованием видеозаписи и видеонаблюдения в развитых странах мира. Предложены пути модернизации и дальнейшего развития систем безопасности в Украине.
Security systems’ status with the use of technical means of video recording and video surveillance: international experience, perspectives for implementation in the activities of the National police of Ukraine
Состояние систем безопасности с использованием технических средств видеозаписи и видеонаблюдения: зарубежный опыт, перспективы внедрения в деятельность Национальной полиции Украины
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; Национальная полиция Украины; National police of Ukraine; поліція; поліція; police; система безпеки; система безопасности; security system; відеозапис; видеозапись; video recording; відеоспостереження; видеонаблюдение; video surveillance; штучний інтелект; искусственный интеллект; artificial intelligence; зарубіжний досвід; зарубежный опыт; foreign experience